University Students' Attitudes towards Biotechnological Studies - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2010)
The aim of this study is to investigate university Students' attitudes towards biotechnological studies. A questionnaire was administrated to the 222 undergraduate students to assess their attitudes towards biotechnological applications. Results of the study indicated that university students' attitudes towards biotechnological studies showed variations and were content dependent. While there was a broad acceptance of modifying microorganisms, this approval was low in making human and animal foods. However, modification of animals and plants were found to be low compared with other researchs found in literature. Statistically significant differences were found between students from different faculties in terms of the results of the questionnaire and it was found that biology students were particularly supportive of biotechnological studies compared with science education and medical students.
Keywords: Students' attitudes; University students; Biotechnology; HIGH-SCHOOL-STUDENTS; KNOWLEDGE